The Effect of the 5E Learning Cycle Model with Learning Journals on Students' Critical Thinking in Thermochemistry - Burhanuddin Ronggopuro; Muntholib Muntholib; Aman Santoso; Jacky Anggara Nenohai (J-PEK (Jurnal Pembelajaran Kimia), 2025)
Work in the 21st century demands strong critical thinking skills. However, high school students still exhibit relatively low levels of critical thinking ability. Integrating learning journals into the 5E Learning Cycle model represents an educational innovation that enhances these skills. This study compares the critical thinking abilities of students in experimental and control classes using a quantitative quasi-experimental design with a non-equivalent control group. Two classes were involved: an experimental group (35 students) and a control group (34 students), each receiving different treatments. The sampling technique used was simple random sampling. Data were collected using 10 questions based on Ennis's five aspects of critical thinking. The instrument was validated and showed a reliability coefficient of 0.725. The results showed a difference in critical thinking scores between the control and experimental classes. The experimental class, which used the 5E Learning Cycle model supported by learning journals, achieved higher outcomes. This was confirmed by an independent t-test, which yielded a p-value (<0.001) and a higher post-test mean score in the experimental class (26.05). A Cohen’s d value of 2.39 indicated a large effect size, while an N-Gain score of 0.95 showed that the intervention fell into the high category.